Biomimetic properties of engineered periodontal ligament/cementum in dental implants - Anil Mathew; Anna Serene Babu; Arun Keepanasseril (Wolters Kluwer Medknow Publications, 2020)
The conventional concept of osseointegrated dental implants based on direct connection to alveolar bone lacks a structured periodontal ligament (PDL) as in natural tooth. This limits the physiologic and functional efficiency of the implant in cushioning occlusal overload, orthodontic tooth movement, and proprioception. Development of bio-mimetic implants that can satisfy the bio-functional requirements of the natural tooth will be an innovative approach and preliminary researches in this area has been reported. This review includes in vivo studies which reported structural features and functional efficiency of an artificial PDL or cementum developed around dental implants. The electronic search identified 12 animal studies and one human trial which utilized retained or adjacent natural tooth roots, exogenous scaffold materials, dental progenitor cells derived from PDL of extracted tooth root as PDL substitutes. The result of the review is dominated by bio-hybrid implants that used dental follicles separated on the particular embryonic day and cell sheets from immortalized human cells. A summary of the currently available research on artificial PDL/cementum around dental implants highlights the potential need of autologous cell-derived tissues to bioengineer a fully functional implant design